2019
DOI: 10.1103/physrevd.100.056021
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic quantum kinetic theory for massive fermions and spin effects

Abstract: We present the complete first order relativistic quantum kinetic theory with spin for massive fermions derived from the Wigner function formalism in a concise form that shows explicitly how the 32 Wigner equations reduce to 4 independent transport equations. We solve the modified onshell conditions to obtain the general solution and present the corresponding transport equations in three different forms that are suitable for different purposes. We demonstrate how different spin effects arise from the kinetic th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
108
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(111 citation statements)
references
References 56 publications
(76 reference statements)
1
108
0
2
Order By: Relevance
“…The 2) for the free streaming part was recently studied in Ref. [21,22,23,24] for massive quarks, extending the recent development of chiral kinetic theory for massless chiral quarks [36,37,38,39,40,41,42], for which a Berry's curvature in momentum space due to spin projection plays a critical role. The 1) is also expected to be intimately related to the "side-jump" phenomenon in chiral kinetic theory [43,44,45].…”
Section: )mentioning
confidence: 89%
See 1 more Smart Citation
“…The 2) for the free streaming part was recently studied in Ref. [21,22,23,24] for massive quarks, extending the recent development of chiral kinetic theory for massless chiral quarks [36,37,38,39,40,41,42], for which a Berry's curvature in momentum space due to spin projection plays a critical role. The 1) is also expected to be intimately related to the "side-jump" phenomenon in chiral kinetic theory [43,44,45].…”
Section: )mentioning
confidence: 89%
“…A more fundamental treatment of (1.1), that should require a significantly larger effort in the future, would involve a complete analysis of spin density matrix in the full phase space (x, p). The free streaming, collision-less quantum kinetic equation for this case was recently studied in Ref [21,22,23,24]. Our study in this sense can be viewed as providing the collision term in leading log of pQCD.…”
Section: Introductionmentioning
confidence: 85%
“…[43][44][45][46]) and chiral vortical effect (CVE) [31,[47][48][49][50][51] for massless fermions. Recently, the kinetic theory for spin-1/2 massive fermions has been formulated in the WF framework [14,[52][53][54][55], which is very useful in describing the evolution of the spin polarization. This is because the axial vector component gives the spin phase space distribution of fermions.…”
Section: Introductionmentioning
confidence: 99%
“…and k L c,A (j 1 ) and k L c,A (j 2 ) with j 1 , j 2 = 1, 2 are two roots of the energy conservation equation (24) and (25) Latin indices label spatial components in the the CMS. The derivation of (24) is given in Appendix D.…”
Section: A Polarization Ratementioning
confidence: 99%
“…The Wigner functions for spin-1/2 fermions are 4 × 4 matrices. The axial vector component gives the spin phase space distribution of fermions near thermal equilibrium [18,25,31,61]. It can be shown that when the thermal vorticity is small, the spin polarization of fermions from the WF is proportional to the thermal vorticity vector.…”
Section: Introductionmentioning
confidence: 99%